Faktor-Faktor Keterlambatan Diagnosis Kanker Pada Pasien Kanker Payudara : Systematic Review - Zahrah Nabila Shidqi; Lintang Dian Saraswati; Nissa Kusariana; Dwi Sutiningsih; Ari Udiyono (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: Breast cancer is one of the most common cancers and has a high mortality rate in women. Patient-mediated factors and healthcare provider-mediated factors are factors associated with cancer delay. This study aims to identify the factors associated with breast cancer delay.Methods: A systematic review was carried out using the PRISMA without meta-analysis method on articles published in 2012-2021. Article searches were conducted using the ScienceDirect, PubMed, EBSCOhost, and Google Scholar databases.Result: From a total of 256 articles that are relevant to the article search keywords, four articles are eligible for this review.Conclusion : Factors related to patient delay are the level of education. Factors related to system delays and diagnosis delays are the place of residence.